Proyek Pengembangan Cengkeh Lampung: Proyek Cengkeh Negara di Lampung Selatan 1974-1987 - Rizky Khairina; Angga Pusaka Hidayat (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2021)
This paper intends to explain the clove cultivation project in South Lampung during the New Order era. More specifically, the Lampung Clove Development Project (PPCL) was discussed in the 1974-1987 period. This project was carried out as a form of commodity diversification from coffee to cloves. Coffee plants that are no longer productive are replaced with cloves. For a long time, cloves have been an important commodity. Clove cultivation in Lampung can be traced back to the late 19th century as part of the colonial expansion of cultivation in people's gardens. As a result, clove cultivation quickly spread to several areas in Lampung, not only on the coast/near rivers but in non-coastal areas as well as planting cloves. This research uses historical method which consists of heuristic, critique, interpretation, and historiography stages. The sources used are archives, books, newspapers, and oral history interviews. Through these sources, it can be seen that prior to the disbandment, clove cultivation carried out under the coordination of PPCL was able to improve the standard of living of farmers. However, due to overlapping land ownership issues and the large number of land owners selling their land, PPCL eventually disbanded.